2017
DOI: 10.1039/c7ce00709d
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and characterization of boron and nitrogen co-doped diamond crystals under high pressure and high temperature conditions

Abstract: In this study, diamond crystals co-doped with boron and nitrogen were synthesized via a temperature gradient method at 5.3–5.8 GPa and 1300–1550 °C by adding B and N dopants to a system of carbon and an Fe-based solvent catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…The nitrogen impurity content in the C center of the diamond was determined by utilizing the relationship between the infrared absorption coefficient and the nitrogen impurity content. The calculation method for nitrogen content is as follows: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrogen impurity content in the C center of the diamond was determined by utilizing the relationship between the infrared absorption coefficient and the nitrogen impurity content. The calculation method for nitrogen content is as follows: …”
Section: Resultsmentioning
confidence: 99%
“…The nitrogen impurity content in the C center of the diamond was determined by utilizing the relationship between the infrared absorption coefficient and the nitrogen impurity content. The calculation method for nitrogen content is as follows: N C ( ppm ) = μ ( 1130 cm 1 ) / μ ( 2120 cm 1 ) × 5.5 × 25 μ ( 1130 cm 1 ) = [ A false( 1290 .25em cm 1 false) A false( 1370 .25em cm 1 false) ] / 0.31 μ ( 2120 cm 1 ) = [ [ 40 × A false( 2030 .25em cm 1 false) + 87 × A false( 2160 .25em cm 1 false) ] 127 A false( 2120 .25em cm 1 false) ] …”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that as the viscosity of the catalyst decreases, the crystallinity of the crystals is better. 24–26…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that as the viscosity of the catalyst decreases, the crystallinity of the crystals is better. [24][25][26] All spectra of the diamond single crystals show only a very strong and narrow peak near 1332 cm −1 , which was the typical Raman peak of diamond. This proves that the diamond crystals grown in these three contact media systems all had a single sp 3 -carbon structure.…”
Section: Raman Spectroscopy Analysis Of Crystalsmentioning
confidence: 99%
“…According to the earth science research, the pressure at 35 km below the surface is about 1.0 GPa. [11][12][13] From this, it can be estimated that the deep pressure of the lithosphere is about 1.0 GPa. Thus, the pressure interval is determined to be between 0.3 GPa and 1.0 GPa according to the high temperature and high pressure measurement equipment.…”
Section: Introductionmentioning
confidence: 94%